Photolysis of 1-Octene and Molybdenum Hexacarbonyl in Tetrahydrofuran - Card, Roger J.; Omar, Muhammad Nor (Penerbit UKM, 1977)
The photolysis of 1-octene and molybdenum hexacarbonyl in tetrahydrofuran results in isomerization of the olefin. When the concentration of molybdenum hexacarbonyl is greater than 0.05M less than 1 mole of the isomerized olefin is producedfor each mole of molybdenum hexacarbonyl. The efficiency of the isomerization decreases as the concentration of molybdenum hexacarbonyl is increased. Under the condition used, the isomerization was initially rapid, but stopped completely after approximately 10 minutes.